Suppression of Phytochrome-Interacting Factors Enhances Photoresponses of Seedlings and Delays Flowering With Increased Plant Height in Brachypodium distachyon - Hoang, Quyen T. N.; Tripathi, Sharanya; Cho, Jae-Yong; Choi, Da-Min; Shin, Ah-Young; Kwon, Suk-Yoon; Han, Yun-Jeong; Kim, Jeong-Il (Frontiers in Plant Science, 2021)
Phytochromes are red and far-red photoreceptors that regulate plant growth and development under ambient light conditions. During phytochrome-mediated photomorphogenesis, PHYTOCHROME-INTERACTING FACTORs (PIFs) are the most important signaling partners that regulate the expression of light-responsive genes. However, the function of PIFs in monocots has not been studied well. In this study, using RNA interference (RNAi), we investigated the functions of BdPIL1 and BdPIL3, two PIF-like genes identified in Brachypodium distachyon, which are closely related to Arabidopsis PIF1 and PIF3. The expression of their genes is light-inducible, and both BdPIL1 and BdPIL3 proteins interact with phytochromes in an active form-specific manner. Transgenic Brachypodium seedlings with the RNAi constructs of BdPIL1 and BdPIL3 showed decreased coleoptile lengths and increased leaf growth when exposed to both red and far-red light. In addition, the transgenic plants were taller with elongated internodes than wild-type Bd21-3 plant, exhibiting late flowering. Moreover, RNA-seq analysis revealed down-regulation of many genes in the transgenic plants, especially those related to the regulation of cell number, floral induction, and chlorophyll biosynthesis, which were consistent with the phenotypes of increased plant height, delayed flowering, and pale green leaves. Furthermore, we demonstrated the DNA-binding ability of BdPIL1 and BdPIL3 to the putative target promoters and that the DNA-Binding was inhibited in the presence of phytochromes. Therefore, this study determines a molecular mechanism underlying phytochrome-mediated PIF regulation in Brachypodium, i.e., sequestration, and also elucidates the functions of BdPIL1 and BdPIL3 in the growth and development of the monocot plant.